Obstruction after Self-expanding Metallic Stents in Tuberculous Bronchial Stenosis - Kim, Won (Korean J Intern Med, 1995)
Expandable metallic stents seemed to be a good method in tuberculous bronchial stenosis that does not respond to medical therapy. But there was no long-term follow-up study after stents insertion in tuberculous bronchial stenosis. We report a case of obstruction after successful Gianturco metallic stents insertion due to tuberculous bronchial stenosis.